Application of SWOT analysis in the context of the school-based teachers’ continuous professional in Dar es Salaam City, Tanzania - Fadhili Ahamad Silim; Moshi Amsi Mislay; Raymond Mwemezi Boniface (Cogent Education)
This study examined the use of SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) in implementing School-Based Teachers’ Continuous Professional Development (SB-TCPD) in selected secondary schools in Dar es Salaam, Tanzania. Data were collected from 15 participants, including school leaders and teachers, through interviews, focus groups, and document reviews, and analyzed thematically. Key strengths identified included teachers’ internal competencies, strategic planning, dedicated budgets, experienced mentors, use of digital platforms like WhatsApp, and a supportive school culture. Weaknesses involved poor ICT integration, limited curriculum understanding, inadequate science pedagogy skills, low English proficiency, and gaps in inclusive education. Opportunities came from supportive policies, stable governance, educational partnerships, active subject panels, and internet access. Threats included inadequate government funding, reliance on external donor projects, and competition from private schools. To address challenges, schools employed strategies such as mentoring, team teaching, internal training, public-private partnerships, and competitive academic programs. The implementation of SB-TCPD led to improved teaching practices, enhanced teacher skills, and better student outcomes. The study highlights the effectiveness of SWOT analysis as a strategic, context-sensitive tool for guiding teacher development, offering practical and participatory approaches tailored to the unique teachers’ needs and resources of each school setting.